2013
DOI: 10.1109/tgrs.2013.2260343
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Radiometric Remote Sensing of Volcanic Ash Clouds From Space: Model and Data Analysis

Abstract: The potential of satellite passive microwave sensors to provide quantitative information about near-source volcanic ash cloud parameters is assessed. To this aim, ground-based microwave weather radar and spaceborne microwave radiometer observations are used together with forward-model simulations. The latter are based on 2-D simulations with the numerical plume model Active Tracer High-Resolution Atmospheric Model (ATHAM), in conjunction with the radiative transfer model Satellite Data Simulator Unit (SDSU) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The MAP estimation of ash class c corresponds to the maximization with respect to c of the posterior pdf p(c|x m ) under the assumption of multivariate Gaussian pdf's. So far, VARR outputs have been tested with ground data in Marzano et al (2012b) and compared with satellite data and plume model simulations in Montopoli et al (2013) providing reasonable results when C-band radar data are used.…”
Section: Retrieval Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MAP estimation of ash class c corresponds to the maximization with respect to c of the posterior pdf p(c|x m ) under the assumption of multivariate Gaussian pdf's. So far, VARR outputs have been tested with ground data in Marzano et al (2012b) and compared with satellite data and plume model simulations in Montopoli et al (2013) providing reasonable results when C-band radar data are used.…”
Section: Retrieval Resultsmentioning
confidence: 99%
“…9 shows a quantitative comparison between SSMIS, DPX and SPC in terms of total columnar concentration (TCC) of C a . SPC is the single polarization C-band radar in Keflavik (260 km away from the Grímsvötn caldera, Montopoli et al, 2013). For the comparison of Fig.…”
Section: Retrieval Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compare model simulations to actual observations in a homogeneous way can help to choice the input model parameters as well as selecting the proper (more reliable) model scenarios that can be used, for example, to address the solution inverse problems. As already proposed in [7], Figure 5 shows a quantitative comparison between BTH [K] at 183 ± 6 GHz from SSMIS and TCC [kg/m 2 ] form DPX. TCC is derived integrating along the vertical direction the mass concentration from VARR-PX shown in figure 2 panel e).…”
Section: Resultsmentioning
confidence: 86%
“…The case study considered is the Grímsvötn eruption on 22 nd of May 2011 in Iceland. Details of ATHAM set-up for the case study here analyzed can be found in [7]. …”
Section: Introductionmentioning
confidence: 99%